Peptidni agonisti receptorja za glukagonu podobni peptid-1 ter njihova uporaba pri zdravljenju sladkorne bolezni tipa 2 in debelosti - Deželak, Matjaž (Farmacevtski vestnik, 2013)
In the beginnings of pharmaceutical, pharmacological, and pharmacotherapeutical sciences small molecules played the main role as chemical synthesis, purification, and drug delivery and targeting were relatively simple. Moreever, high degree of chemical stability and biological availability both worked in their favour. Later on, technologies for achieving the appropriate degree of above mentioned limiting factors improved, and larger, polymeric molecules became useful. Among them, the most important are peptides and proteins, which have crucial natural role in organisms physiology. This review article discusses peptide drugs in general and it continues with glucagon like peptide-1 (GLP-1) being used for treatment of diabetes mellitus type 2 and obesity. Because of the fact that the peptide drug-based therapy of these two illnesses is relatively new it still has quite some imperfections. That is why directions to achieve a better treatment efficacy which are based on our latest research are presented at the end.
Keywords: debelost; obesity; peptide drugs; peptidne učinkovine; sladkorna bolezen tipa 2; type 2 diabetes mellitus